Case Report: Primary lymphoepithelioma-like intrahepatic cholangiocarcinoma - Liu, Fei; Xu, Qing; Regmi, Parbatraj; Li, Fu-Yu; Lin, Yi-Xin (Frontiers in Oncology, 2023)
Background: Lymphoepithelioma-like intrahepatic cholangiocarcinoma (LEL-ICC) is a rare variant of intrahepatic cholangiocarcinoma. Epstein–Barr virus (EBV) infection was considered to play a pivotal role in the tumorigenesis of LEL-ICC. It is difficult to diagnosis of LEL-ICC due to the lack of specific features regarding the laboratory test results and imaging findings. At present, the diagnosis of LEL-ICC mainly depends on the histopathologic and immunohistochemical examinations. In addition, the prognosis of LEL-ICC was better than classical cholangiocarcinomas. To our knowledge, only few cases of LEL-ICC have been reported in the literature. Case presentation: We presented a case of a 32-year-old Chinese female with LEL-ICC. She had a 6-month history of upper abdominal pain. The magnetic resonance imaging (MRI) showed a 1.1× 1.3 cm lesion in the left lobe of liver, appearing low signal intensity on T1-weighted images and high signal intensity on T2-weighted images. The patient underwent laparoscopic left lateral sectionectomy. The postoperative histopathologic and immunohistochemical examinations results allowed for the definitive diagnosis of LEL-ICC. The patient was free from tumor recurrence after a 28 months follow-up. Conclusion: In this study, we reported a rare case of LEL-ICC associated with both HBV and EBV infection. EBV infection might play a pivotal role in the carcinogenesis of LEL-ICC, and surgical resection is still the most effective treatment at present. Further research on the etiology and treatment strategies of LEL-ICC is required.